HEMOGLOBIN LEVELS AS RISK FACTOR OF LOW BIRTH WEIGHT - Fitriana Ciptaningtyas; Irwanto Irwanto; Widati Fatmaningrum (Indonesian Midwifery and Health Sciences Journal, 2022)
Abstract   Background: There are still mothers with low hemoglobin levels who gave birth to babies with Low birth weight in Wonosamodro District Boyolali. The study's objective was to study the correlation between LBW and hemoglobin levels at Puskesmas Wonosamodro Boyolali. Methods: The research implemented an analytical observational method with a case-control design to collect information on identity, hemoglobin levels, and birth weight utilizing MCH books. The total population of the case group was 98 toddlers and the control group population was 2184 toddlers. The sample size was 51 children under five in each case and control group. The sampling method used consecutive sampling and matching sampling. The statistical test used the chi-square test. Result: p value of Hb 3rd trimester=0,01 showed that hemoglobin levels during pregnancy had a correlation with LBW. OR=3,540 95% CI 1,427-8,782 showed that mothers with anemia in the 3rd trimester have 3,5 times the risk of having low birth weight babies. Conclusion: Mother’s hemoglobin levels is correlatted with LBW in Wonosamodro, Boyolali. Efforts are needed to maintain and improve maternal health to reduce the risk of low birth weight. Keyword : LBW, hemoglobin, anemia